Home Sweet Home: The Tumor Microenvironment as a Haven for Regulatory T Cells - Ondondo, Beatrice O.; Gallimore, Awen; Jones, Emma; Godkin, Andrew (Frontiers in Immunology, 2013)
CD4+Foxp3+ regulatory T cells (Tregs) have a fundamental role in maintaining immune balance by preventing autoreactivity and immune-mediated pathology. However this role of Tregs extends to suppression of anti-tumour immune responses and remains a major obstacle in the development of anti-cancer vaccines and immunotherapies. This feature of Treg activity is exacerbated by the discovery that Treg frequencies are not only elevated in the blood of cancer patients, but are also significantly enriched within tumours in comparison to other sites. These observations have sparked off the quest to understand the processes through which Tregs become elevated in cancer-bearing hosts and to identify the specific mechanisms leading to their accumulation within the tumour microenvironment.